Association between the CYP24A1 rs2762939 polymorphism and vascular calcification in Indonesian patients with chronic kidney disease on hemodialysis - Wendy, Wendy; Muzasti, Riri A.; Tarigan, Radar R. (Narra Sains Indonesia, 2025)
Vitamin D plays a key role in mineral metabolism, and its dysregulation contributes to vascular calcification, a major complication of chronic kidney disease–mineral and bone disorder (CKD–MBD) in patients undergoing hemodialysis with CKD. The CYP24A1 gene encodes 24-hydroxylase, the enzyme responsible for degrading active vitamin D metabolites and its polymorphisms, particularly rs2762939, have been linked to variability in vitamin D status and coronary artery calcification. The aim of this study was to assess the association between the rs2762939 polymorphism of CYP24A1 and vascular calcification in Indonesian patients with CKD undergoing maintenance hemodialysis. A case–control study was conducted in 92 hemodialysis patients, including 46 with vascular calcification and 46 without. Genotyping of the rs2762939 polymorphism was carried out using PCR–RFLP, and the amplified products were separated by electrophoresis on 4% agarose gel. The frequency of vascular calcification was found to be significantly higher in patients with diabetes mellitus than in the control group (19 (82.6%) vs 4 (17.4%)), whereas in non-diabetic patients the frequency of vascular calcification was lower compared with controls (27 (39.1%) vs 42 (60.9%)). A statistically significant association between CKD etiology and vascular calcification was observed (p=0.001). The prevalence of vascular calcification was lower among carriers of the mutant C allele (45%) compared with the G allele (51.4%), although this difference was not statistically significant (OR=0.77; 95%CI: 0.38–1.56; p=0.592). The rs2762939 polymorphism of the CYP24A1 gene was not significantly associated with vascular calcification in Indonesian patients with CKD undergoing maintenance hemodialysis. Further studies with larger, ethnically diverse cohorts and integration of vitamin D status are needed to clarify the genetic contribution of CYP24A1 and related pathways to vascular calcification.